2017
DOI: 10.21273/horttech03710-17
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Market Potential for Specialty Cultivars of Sunflower Cut Flowers

Abstract: In the United States, there is an increasing demand for field- or greenhouse-grown, specialty, locally grown cut flowers. However, certain cultivars of cut flowers are not readily available in the market. The purpose of this research was to produce a crop of novelty sunflowers (Helianthus annuus ‘Firecracker’) and study the marketability of the cut flowers to wholesale and retail florists and consumers. The plants were grown in greenhouses. Stems were harvested and shown to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…These findings were consistent with other horticultural product purchasing studies. For example, Short et al (2017) found no difference in WTP regarding locally grown specialty cut sunflowers based on age, income, and education. LOCALITY SCORE COMPARISONS.…”
Section: Demographic Comparisons Of W I L L I N G N E S S T O P a Y A M O N Gmentioning
confidence: 98%
See 3 more Smart Citations
“…These findings were consistent with other horticultural product purchasing studies. For example, Short et al (2017) found no difference in WTP regarding locally grown specialty cut sunflowers based on age, income, and education. LOCALITY SCORE COMPARISONS.…”
Section: Demographic Comparisons Of W I L L I N G N E S S T O P a Y A M O N Gmentioning
confidence: 98%
“…Targeting farmers' market patrons allowed researchers to include individuals in the study who were predisposed to participating in niche markets. This type of relationship marketing has been used to predict consumer behavior and potential markets in past studies (Shani and Chalasani, 1992;Short et al, 2017).…”
Section: Brown Seaweed Compostmentioning
confidence: 99%
See 2 more Smart Citations
“…The final section consisted of seven demographic questions asking respondents to provide their age, education level, annual household income, gender, and ethnicity. These were based on a reliable instrument used in a previous similar study (Short et al, 2017).…”
Section: Perceptions Of Environmental Health and Willingness To Compostmentioning
confidence: 99%